Caring for Young Adults With Diabetes in the Adult Care Setting: Summary of a Multidisciplinary Roundtable - Toschi, Elena; Leblanc, Jennifer; Hafida, Samar; Mehta, Sanjeev; Ritholz, Marilyn; Gabbay, Robert; Laffel, Lori (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aims: A multidisciplinary team of clinicians and researchers, patients and family members, and representative from national advocacy groups and research organization met to review the literature, highlight gaps, and identify best practices to improve adult care delivery for young adults (YA) with diabetes. Methods: The participants prepared presentations in advance, rotated through sessions, and contributed to group discussions in three areas: physical health, mental health, and quality of life (QoL). Session moderators and scribes used thematic analysis to summarize discussions for each topic. Results: Thematic analysis revealed four foci for addressing physical health, mental health and QoL: 1) best practices to facilitate the process of transfer; 2) age-specific curricula and guidelines for prevention and management of comorbidities and complications; 3) collaboration with behavioral health clinicians to address diabetes distress and mental health disorders; and 4) research on the impact of diabetes on QoL in YA. Conclusion: There was substantial interest and need among adult clinicians to work in concert with pediatric and mental health professionals to identify best practices and future directions to improve healthcare process and diabetes-related outcome measures in YA with diabetes.